2019
DOI: 10.1002/dvdy.37
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of in vitro fertilization with frozen‐thawed sperm: An analysis of post‐thaw recovery of sperm, embryogenesis, offspring morphology, and skeletogenesis for a cyprinid fish

Abstract: Background Gamete cryopreservation causes cellular damage and death. This study develops cryopreservation techniques for Levantine scraper, and deciphers how early offspring development is affected when eggs are sired with fresh and frozen‐thawed sperm. Results Cryopreserved sperm did not affect embryogenesis at two‐ and four‐cell stages, but impaired embryonic development at eight‐cell stage. Embryonic viability decreased at organogenesis, where only 34‐49% of embryos showed viability with frozen‐thawed sperm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“…71 The long-term health consequences of manual handling and cryopreservation-induced DNA damage on resultant offspring are poorly understood but have been associated with increased incidences of poorer outcomes such as epigenetic disorders, DNA methylation and morbidity in animal studies. [72][73][74] As a method to determine if maternal complications such as preeclampsia had an effect on health outcomes in the cohorts, the data were stratified into those who reported that their mother had maternal complications and those whose mother did not. As was the case with analysis of sex differences, the sample size for those reporting maternal complications in the donor spermconceived cohort of N = 47 reduced the power to detect differences in the donor sperm cohort.…”
Section: Discussionmentioning
confidence: 99%
“…71 The long-term health consequences of manual handling and cryopreservation-induced DNA damage on resultant offspring are poorly understood but have been associated with increased incidences of poorer outcomes such as epigenetic disorders, DNA methylation and morbidity in animal studies. [72][73][74] As a method to determine if maternal complications such as preeclampsia had an effect on health outcomes in the cohorts, the data were stratified into those who reported that their mother had maternal complications and those whose mother did not. As was the case with analysis of sex differences, the sample size for those reporting maternal complications in the donor spermconceived cohort of N = 47 reduced the power to detect differences in the donor sperm cohort.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, sperm motility, fertilization rate and the hatching rates were seen to be high and similar with postthaw semen when compared with use of fresh semen in some Salmoniforms and Esociformes [19][20][21] . On the other hand, studies done so far on few other teleosts (e.g., Levantine scraper, wild brown trout, Atlantic cod) report reduced motility and viability of sperm after freezing-thawing 22 . Also, the post-thaw semen from the same fish when used for in vitro fertilization, there were significant declination in fertilization success when compared with fresh sperm control, followed by abnormalities like cleavage patterns, hatching success, organogenesis etc.…”
Section: Introductionmentioning
confidence: 92%
“…On the other hand, studies done so far on few other teleosts (e.g. Levantine scraper, wild brown trout, Atlantic cod) report reduced motility and viability of sperm after freezing-thawing 25 . Also, the post-thaw milt from the same fish when used for in vitro fertilization, there were significant declination in fertilization success when compared with fresh sperm control, followed by abnormalities like cleavage patterns, hatching success, organogenesis etc.…”
Section: Introductionmentioning
confidence: 92%